2021
DOI: 10.1111/pcmr.13024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a SLC24A5 variant on the retinal pigment epithelium of a Japanese patient with oculocutaneous albinism type 6

Abstract: Oculocutaneous albinism (OCA) 6 is a non‐syndromic type of OCA that has distinct ocular symptoms and variable cutaneous hypopigmentation. The causative gene of OCA6 is SLC24A5, which encodes NCKX5, a K+‐dependent Na+/Ca2+ exchanger 5. NCKX5 is involved in the maturation of melanosomes, but its function is still unclear. In this study, we characterized a Japanese patient with OCA6. Genetic analysis revealed compound heterozygous variants in SLC24A5, c.590 + 1dupG, and c.598G>A (p.G200R). To clarify the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…PM has been demonstrated to contribute to carcinogenesis through both UV‐dependent and UV‐independent pathways through the production of reactive oxygen species (Mitra et al., 2012). We previously reported that patients with oculocutaneous albinism (OCA) and Hermansky‐Pudlak syndrome (HPS) exhibit significantly elevated levels of 4‐AHP, a marker of BT‐PM that is potentially associated with a high risk of skin cancer (Okamura et al., 2018; Saito et al., 2022). In this case, there was a substantial reduction in both EM and PM, thus raising concerns regarding UV‐induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…PM has been demonstrated to contribute to carcinogenesis through both UV‐dependent and UV‐independent pathways through the production of reactive oxygen species (Mitra et al., 2012). We previously reported that patients with oculocutaneous albinism (OCA) and Hermansky‐Pudlak syndrome (HPS) exhibit significantly elevated levels of 4‐AHP, a marker of BT‐PM that is potentially associated with a high risk of skin cancer (Okamura et al., 2018; Saito et al., 2022). In this case, there was a substantial reduction in both EM and PM, thus raising concerns regarding UV‐induced carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no direct evidence that SLC24A2 is related to skin hair follicles, SLC24A5 has been con rmed to be related to animal hair color (Jorgenson et al 2020). RT-PCR results showed that the SLC24A5 gene was highly expressed in skin and eyes and low expressed in other tissues, while the expression level in mouse melanoma was more than 100 times higher than that in normal skin and eyes (Childebayeva et al 2022;Saito et al 2022). Our previous research showed that SLC24A2 is a key molecule in hair follicle development signal transduction which also is the target gene of the oar-miR-377 by microRNA-sequencing analysis.…”
Section: Introductionmentioning
confidence: 92%
“…SLC24A5 also regulates melanin changes in other vertebrate species, such as mice and zebrafish. In addition, mutations in SLC24A5 can cause non-syndromic oculocutaneous albinism (Ju & Mathieson, 2021;Lin et al, 2018;Saito et al, 2022;Wei et al, 2013). In the mouse, the most common model animal, Slc24a5 protein plays an important role in the neuroepithelial pigment cells of the mouse eye.…”
Section: Box 2 the Contribution Of Crucial Pigmentation Genes To The ...mentioning
confidence: 99%